Relationship Between Diet, Anemia Status, and Youth Women’s Physical Activity with The Incidence of Dysmenorrhea at SMA Negeri 1 Rote Timur in 2022 - Lay, Soleman Ayub; Nur, Marselinus Laga; Toy, Sarci Magdalena (Faculty of Public Health, Nusa Cendana University, 2024)
Dysmenorrhea is a symptom not a disease. Complaints that are usually felt by women or young women when experiencing dysmenorrheal are experiencing cramps/pain in the lower abdomen, but can radiate to the waist, pelvis, back of the back, even pain in the thigh and calf muscles. Menstrual pain in influenced by between diet, anemia status and physical activity. This study aims to determine the relationship between diet, anemia status, and youth women’s physical activity with the incidence of dismenorrhea at SMA Negeri 1 Rote Timur 2022. The type of research used was an analytic observational study with a case control design. The population used for this study were all students in grades X, XI and XII of SMAN 1 Rote Timur, consisting of 369 students. A sample of 37 cases and 37 controls using simple random sampling (simple random sampling). The research instrument is a questionnaire. The analysis techniques in this study were univariate, bivariate and chi square tests. Univariate results showed that 52,7% of respondents had a bad amount of food, 63.5% of respondents had more than 5 types of eating, 63.5% of respondents had a frequency of eating more than 3 times a day, 52,7% of respondents who have a anemia status, 68.9% of respondents who have sufficient activity. The bivariate results showed that there was a relationship between the amount of food (p=0.000) and anemia status (p=0.005) with the incidence of dysmenorrhea and there was no relationship between the type of food (p=0.334), frequency of eating (p=0.334) and physical activity (p=1.000 ) with the incidence of dysmenorrhea in SMA Negeri 1 Rote Timur.